Faster Return to Intended Oncologic Treatment (RIOT) After Trisectionectomy Does Not Translate to Better Outcomes. Issue 2 (February 2021) - Baimas-George, Maria; Watson, Michael; Pickens, Ryan C.; Sulzer, Jesse; Murphy, Keith J.; Ocuin, Lee; Baker, Erin; Martinie, John; Iannitti, David; Vrochides, Dionisios
Background: Resection with trisectionectomy may necessitate liver molding for adequate future liver remnant (FLR), and subsequent complications can impact return to intended oncologic therapy (RIOT). This study evaluated whether a difference in RIOT exists with the use of molding and between liver molding techniques (associating liver partition and portal vein ligation for staged hepatectomy [ALPPS] and portal vein embolization [PVE]) with trisectionectomy. Methods: A retrospective review evaluated trisectionectomies for malignancy. Outcomes were compared with and without molding, and RIOT was determined. Results: Fifty-one patients underwent trisectionectomy: 11 ALPPS, 14 PVE, 26 without molding. 73% of ALPPS, 64% of PVE, and 58% without molding achieved RIOT ( P = .971). There were no differences found in baseline characteristics, R0 rate, length of stay, readmission, complications, or mortality. Time to RIOT was significantly different (ALPPS: 3.3 months; PVE: 5.2 months; none: 2.4 months, P = .0203). There were no differences in recurrence or survival. Conclusions: Liver molding should not cause apprehension as there are no differences in achieving RIOT. Although technique alters time to RIOT, this does not translate into improved outcomes, implicating disease biology, and regeneration stimulus.